"De novo" familial adenomatous polyposis (FAP) presenting as rectal cancer. Issue 5 (5th May 2021) - Agrawal, Riya; De, Utpal
Abstract: Familial adenomatous polyposis is an autosomal dominant disorder with familial predisposition. 25%‐30% cases arise "de novo, " without any clinical or genetic evidence. Abstract : Familial adenomatous polyposis is an autosomal dominant disorder with familial predisposition. 25%‐30% cases arise "de novo, " without any clinical or genetic evidence.